(untitled) (Research, Society and Development, 2025)
The extension project “Indigenous Adult Health in the Amazon: Sociocultural Perspectives and Suicide Prevention Strategies” was developed in the Kainã Village, in Manaquiri (AM), within the “Caring for the Amazon” program, aimed at promoting the health of indigenous and riverside populations. The objective of the project was to understand and intervene in a humane way in the health of the Kainã Village, belonging to the Munduruku ethnic group, focusing on suicide prevention. Nursing students from the 6th semester addressed different aspects of indigenous health. Activities included a nursing station for data collection and anamnesis, discussion groups, educational workshops, and a theatrical performance on women’s health, menopause, contraception, and mental health. There was also a celebration of Children’s Day, with donations and games. Dialogue with the community reinforced the importance of active listening, emotional support, and valuing traditional knowledge, which strengthens cultural identity and mental health prevention.